English Teachers’ Strategies in English Online Learning during Covid-19 Pandemic - Dian Helfia Putri; Yon A E (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The purpose of this study was to see the effect of the English teacher's strategy in teaching English on the students' ability to receive English material during online classes during the Covid-19 pandemic at SMPN 31 Bekasi. The writer uses quantitative data to collect the data collected by using the English teacher strategy questionnaire. The population of this study were students in grades 8 and 9 as many as 83 students, while the sample size was taken as many as 45 students. The data analysis tools used are normality test, simple regression analysis, simple correlation analysis, Coefficient of deterprestasiion and Hypothesis Testing with t Test. The regression equation is obtained Y= 0.373 + 0.626 X. The equation shows that the coefficient value for the online learning strategy of English teachers during Covid-19 (X) in this study had a negative effect on student learning outcomes (Y) at SMPN 31 Bekasi. The correlation between the English teachers’ strategies on students' understanding during online learning was obtained r = 0.949, means the relationship between English teachers’ strategies on students' understanding during online learning at SMPN 31 Bekasi is very strong. While the results of the coefficient of determination ( r2 ) = 89.9%, this means that the variable English teachers’ strategies variables can affect students' understanding of material at SMPN 31 Bekasi is 89.9% while other variables affect students' material understanding by 10.1%. Hypothesis testing results obtained tcount = 19.833 and the value of ttable = 1.684. Because the value of tcount > ttable is shown, H0 is rejected while Ha is accepted. This means that the English teachers’ strategies in online learning during the Covid-19 pandemic has a significant influence on students' understanding of material during online learning at SMPN 31 Bekasi.